ANION RECOGNITION BY AMIDE-LINKED PYRIDYL AND PYRIDINIUM SUBSTITUTED COBALTICINIUM RECEPTORS - Beer, P; Stokes, S (1995)
New acyclic mono- and 1,1′-bis-amide-linked pyridyl and pyridinium substituted cobalticinium ligands have been prepared. 1H NMR anion coordination studies reveal that these ligands form 1 : 1 stoichiometric solution anion complexes with halides, HSO4- and H2PO4-. Stability constant determinations suggest that the pyridinium cobalticinium derivatives form stronger chloride anion complexes than their pyridyl analogues. Cyclic voltammetric investigations show that all these new cobalticinium derivatives electrochemically recognize halide, HSO4- and H2PO4- guest anions. © 1995.